Taxa de câmbio e competitividade internacional dos setores de transformação da economia brasileira - Rodrigues, Elizeu Elias (Universidade Federal de São Carlos, 2015)
This research aims to investigate the relation that exists between the exchange rate and the international competitiveness of the Brazilian transformation industries classified by level of technology. It begins with a synthesis of the several studies that show the importance of the exchange rate to the development of the country and, particularly to the Brazilian case, it highlights those that point a domestic currency appreciation and stress that appreciation is contributing to put the country down in backward position in technological terms. Therefore, some authors propose the Real should be depreciated relative to Dollar to promote an internal productive diversification and the sophisticated sectors development. That discussion motived us making econometrical analyses and graphics linking exchange rate, exports and international competitiveness index to investigate if exchange rate variations impacted in determinant form and distinctly the internacional competitiveness of Brazilian industries. The methodology was used the revealed comparative advantage (RCA) index of Balassa (1965) and VAR models to connect exchange rate and industries exports. The RCA index time evolution was analyzed in graphics together with the exchange rate from 1999 until 2011. The results has been showed that occurred a loss of competitiveness to the majority of national industries and exchange rate appreciation most of the analyzed period still affected the industries in the distinct manner. Finally, almost all industries did not get competitiveness gains in the period of exchange rate depreciation as expected, because they did not have enough time to react.
Keywords: Vantagem comparativa (Comércio); Comparative advantage (International trade); Taxas de câmbio; Foreign exchange rates; Comércio internacional; International trade; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INTERNACIONAL::RELACOES DO COMERCIO; POLITICA COMERCIAL; INTEGRACAO ECONOMICA